Association between plasma free haem and incidence of vaso‐occlusive episodes and acute chest syndrome in children with sickle cell disease. (27th June 2013) - Adisa, Olufolake A.; Hu, Yijuan; Ghosh, Samit; Aryee, Doreen; Osunkwo, Ifeyinwa; Ofori‐Acquah, Solomon F.
Summary We tested the hypothesis that extracellular haem is linked to the incidence of acute complications of sickle cell disease (SCD). Using multivariable regression analysis, higher plasma free haem, but not total plasma haem, was associated with increased odds of vaso‐occlusive crisis (VOC) [P = 0·028, odds ratio (OR); 2·05, 95% Confidence Interval (CI) = 1·08–3·89] and acute chest syndrome (ACS) [P = 0·016, OR; 2·56, CI = 1·19, 5·47], after adjusting for age and gender in children with SCD. These findings suggest that haem and factors that influence its concentration in plasma may be informative of the risk of VOC and ACS in SCD patients.